Features of the phase and structural transformations in the processing of industrial waste from the production of highalloyed steels - Borysov, Viacheslav; Lytvynov, Andrii; Braginets, Nikolai; Petryshchev, Artem; Artemev, Sergey; Tsymbal, Bohdan; Poliakov, Anatolii; Bratishko, Viacheslav; Kuzmenko, Volodymyr; Kholodiuk, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2020)
We have investigated the physical and chemical properties of the alloy obtained by reduction smelting using wastes from the production of highly-alloyed steels and alloys. This is necessary to determine the technological aspects that reduce the loss of doping components when obtaining and using a doping alloy. The study results indicate that at the charge's oxygen-to-carbon ratio of 2.25, the alloy consisted mainly of a solid solution of doping elements in γ-Fe. At the charge's oxygen-to-carbon ratio of 1.67, we also observed Fe3C, followed by an increase in the intensity of carbide manifestation at the oxygen-to-carbon ratio of 1.19. Photographs of the microstructure clearly showed several phases with a different ratio of doping elements. The Ni content in the examined sections of various phases changed within 1.38‒46.38 % by weight, Cr ‒ 3.45‒45.32 % by weight, W ‒ 1.51‒27.32 % by weight, Mo ‒ 0.48‒10.38 % by weight. Mo, W, Nb mostly concentrated in individual particles. The Nb content in some inclusions reached 47.62 % by weight. Analysis of the study results has shown that the most beneficial charge's oxygen-to-carbon ratio is 1.67. At the same time, the phase composition is dominated by a solid solution of doping elements in γ-Fe. The proportion of residual carbon, which was in the form of a carbide component, accepted values in the range of 0.52‒2.32 % by weight while providing the necessary reducing capacity when using the alloy. Our research has identified new technological aspects in the processing of highly-alloyed anthropogenic waste when obtaining an alloy with a relatively low residual carbon content. The resulting parameters of the resource-saving doping material ensure the possibility to replace some of the standard ferroalloys when smelting steels with certain carbon content restrictions.